37.0k views
4 votes
Simplify (9 + 8 – 6)(4 – 5).

User Yanire
by
6.0k points

2 Answers

4 votes

Answer:

-11

Explanation:

Use PEMDAS

P Parentheses first

E Exponents

MD Multiplication and Division

AS Addition and Subtraction

P

(9 + 8 - 6)(4 - 5) = (17 - 6)(-1) = (11)(-1)

M

= -11

User Rattek
by
5.2k points
5 votes

Answer:

The answer would be - 11.

Explanation:

9 + 8 = 17

17 - 6 = 11.

4 - 5 = 4 + - 5 = - 1

11(- 1) = 11 × - 1 = - 11

Therefor, your answer would be - 11.

Hope this helps!

User Mostafa Aghajani
by
5.4k points